(untitled) (Journal of the College of Basic Education, 2026)
This study, titled "The Natural Symbol in Fawzi al-Ta’i’s Resistance Poetry," presents an interpretive analysis of how natural symbols function as expressive tools in al-Ta’i’s poetic depiction of national suffering and resistance against occupation and oppression. The research is structured into two main sections. The first outlines the theoretical framework, defining key concepts such as "symbol" and "resistance," and exploring the connection between symbolism and resistance poetry. It also provides a biographical overview of Fawzi al-Ta’i and his role in modern Iraqi and Arab poetry. The second section offers a detailed analysis of selected poems, examining how elements of nature are employed to convey collective resistance and articulate the poet’s vision. The study adopts a descriptive-analytical methodology grounded in symbolic nterpretation, contextualizing the poems within psychological, social, and political dimensions to uncover the aesthetic and ideological functions of natural symbolism. Among its key findings, the research concludes that the natural symbol in al-Ta’i’s poetry serves as a semantic vehicle that conveys his intellectual and militant stance. His use of symbolism is marked by depth, subtlety, and layered meaning, reflecting a heightened poetic consciousness of homeland, identity, and struggle.